Heat-shock induction time and levels of loss of bone mineralization in the osteoporosis medaka fish model rankl:HSE:CFP subline c1c8 - Thi Minh Tam, Ha; Thi Thuy Trang, Tran; Van Cuong, Pham; Thi Thanh, Pham; Duc Long, Tran; Thanh Thuy, To (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2SDO - 10.25073/2588-1140/vnunst.4617, 2017)
The transgenic medaka fish ( Oryzias latipes) rankl :HSE:CFP expressing Rankl, a stimulator for osteoclastogenesis, is used as an osteoporosis model to screen for antiosteoporosis substances. In this fish, rankl expression is regulated by a heat inducible promotor. Therefore, upon heatshock at 39 o C, the fish expresses ectopic Rankl, which promotes formation and activity of osteoclasts, leading to bone mineralization damage and osteoporosis-like phenotype. However, how the level of mineralization damage depends on heatshock induction time still has been an open question that we aimed to answer  in this study. To this end, 9-day-post-fertilization (dpf) rankl :HSE:CFP fish larvae of subline c1c8 were divided into 5 groups that were heatshocked at 39°C for 30, 60, 75, 90 or 120 minutes. Level of loss of bone mineralization of fish larvae in each group was assessed at 11dpf by their bone mineralization index. Results showed that levels of bone loss of these fish groups were 33, 62, 65, 79 or 93%, respectively, and correlated well and directly proportional with heat-shock duration. These results provide important data that help establishing procedures and protocols for using the fish in further studies on bone.